Pengkaderan Da’iah Melalui Pelatihan Retorika Dakwah (Kelompok Kajian Ibu-Ibu ‘Cengkir Gati’ di Dusun Sawahan Nogotirto Gamping Sleman) - Syahdara Makruf; Maisaroh Maisaroh (Jurnal Abdimas Madani dan Lestari (JAMALI), 2019)
Training cadre is a learning process that is carried out in stages and continuously in accordance with the levels, achievements, situations and specific needs that enable a cadre to develop all his potential potentials, physical abilities, and social morals. Preaching rhetoric is the art of talking about influencing others through messages. It is a branch of communication science that discusses how to convey messages to others through the art of talking so that preaching messages can be received. Through a series of dedication activities under the title of Development of Islamic Life Quality Improvement Model which is carrying out the regeneration of the community through training on methods and motivation in preaching, and microteaching / practicing. This service is expected to be able to answer the problems of the community in order to stay alive the Mother Study group 'Cengkir Gati' in Dusun Sawahan Nogotirto Gamping Sleman, Region of Yogyakarta.  Keywords: Cadre, Rhetoric, Preaching